The Influence of Accounting Information Systems and Service Systems on Organizational Performance at Hospital in Makassar City - Husna, Asmaul; Pontoh, Grace T; Indrijawati, Aini (KINERJA, 2023)
This study aims to analyze the accounting information system in hospitals. This study uses primary data sources by distributing questionnaires to 63 respondents with research samples, namely the head of service, head of support, and head of financial administration at type A and type B hospitals in Makassar City. The returned questionnaire was 57 respondents, processed using multiple linear analysis with the help of the SmartPLS computer program. The results showed that the accounting information system and service system have a role in improving organizational performance at hospitals in Makassar City.